Faktor -faktor yang Berhubungan dengan Pemilihan Kontrasepsi Iud di Puskesmas Sungai Jambat Kecamatan Sadu Kabupaten Tanjung Jabung Timur Provinsi Jambi - Lubis, Sunarti; Rizki, Merisa; Priyanti, Elis (Jurnal Ners, 2023)
Intra Uterine Devices (IUD) is a tool or object that is inserted into the uterus which is very effective, reversible and long term, and can be used by all women of reproductive age. The choice of contraceptive method can be influenced by several factors, namely age, education level, parity, and family income. This study aims to determine the factors associated with the choice of IUD contraception at the Sungai Jambat Health Center. The population of this study were women of childbearing age (PUS). This type of research is an analytic survey with a cross-sectional design. The number of samples in this study was calculated using the Lameshow formula which determined the value of n as many as 85 samples. The data of this research are primary and secondary data. This study was analyzed using univariate and bivariate data analysis. The univariate results showed that the majority had an at-risk age of 46 respondents (54.1%), the majority had a high educational level of 46 respondents (54.1%), the majority parity was not at risk of 63 respondents (74.1%), the majority of high family incomes were 62 respondents (72.9%). From the results of the bivariate Chi-square test, it was found that age with a mother's interest was p=0.074>0.05, educational level with a mother's interest was p=0.000<0.05, parity was with a mother's interest p=0.000<0.05, and family income with an interest in mother p=0.002<0.05. It was concluded that there was a relationship between education level, parity, and family income with the choice of IUD contraception at the Sungai Jambat Health Center, Sadu District, East Tanjung Jabung Regency, Jambi Province in 2022.